ETIKA TANGGUNG JAWAB EMMANUEL LEVINAS - Sobon, Kosmas (Fakultas Filsafat, Universitas Gadjah Mada Yogyakarta, 2018)
This article aims to know and critically analyze the ethical responsibilities of Levinas. He gives a new concept of responsibility. For him, ethics is the first philosophy. The ethics of Levinas's responsibilities must be understood in a metaphysical aspect. The research method used is literature research using hermeneutics method. The essence of Levinas’s responsibility: responsibility as an existential fact, nonnormative, for the others, substitutional, the essential structure of subjectivity, a basis for existence, the responsibility of humanizing himself, and responsibilities make me unique from others. The ethics of Levinas's responsibilities have two characters: concrete and asymmetric.